PENGARUH BIMBINGAN KLASIKAL TERHADAP PENINGKATAN MINAT BELAJAR SISWA MELALUI TEKNIK DISKUSI KELOMPOK DI KELAS VII SMP NEGERI 8 PALOPO - Nur Aulia Muhammad , Balqist; Fahmi, Ainul; Kadir, Abdul (IKIP Siliwangi, 2025)
This study aims to determine the effect of classical guidance services through group discussion techniques on increasing the learning interest of 7th-grade students at SMP Negeri 8 Palopo. The study used a pre-experimental quantitative approach with a One Group Pretest-Posttest Design. The research sample consisted of 13 students from class VII-C selected based on observations and interviews with teachers. Data were collected using questionnaires, observations, and interviews. The results showed a significant increase in students' learning interest after the implementation of classical guidance using group discussion techniques. This was evidenced by a Paired Sample T-Test that yielded a significance value of < 0.05. Thus, group discussion techniques are effective in classical guidance services to enhance students' learning interest.